Architecture and evolution of the Cenozoic offshore Bohai Bay basin, eastern China. (1st May 2020) - Yu, Yixin; Zhou, Xinhuai; Xu, Changgui; Wu, Kui; Lv, Dingyou; Liu, Yubo; Zhou, Xin
Graphical abstract: Highlights: The Cenozoic OBBB has similar graben-horst configurations as in many rift basins. Different subbasins in the OBBB have different timing and stratigraphic fill. The Cenozoic evolution of the OBBB involve rifting and thermal subsidence stages. Basement fabrics and Tanlu fault zone affect architecture and evolution of the OBBB. Abstract: The Cenozoic offshore Bohai Bay basin has similar graben-horst configurations as in many rift basins, however, different areas of it have different stratigraphic fill, resulted from jointly effects of basement fabrics, rifting and strike-slipping. Within the Liaodongwan subbasin, the Liaodong rise is a transpressional structural belt bounded by the Tanlu strike-slip fault. The Bodong rise is similar to the Liaodong rise. The eastern Bozhong subbasin has a graben-horst configuration caused by extensional stress. The southern and northwestern parts of the Bozhong subbasin are characterized by large-scale horsts that are limited by south-dipping listric normal faults. The Bozhong subbasin shows many similarities with the faulted sag basin. The southern Bohai Bay basin is characterized by EW-oriented half-grabens and horsts resulted from S-N extensional stress. The Cenozoic evolution of the basin began with Paleogene rifting, followed by the Neogene–Quaternary thermal subsidence stage. The main rifting episode, caused by the upwelling of the mantle, is characterized by strong differential block-faulting during the deposition of the Eocene Sha-3 member. During the deposition of the Oligocene Dongying Formation, previously isolated and scattered sags connected with each other and became a broad and unified lake basin. In addition, the dextral movement of the Tanlu fault zone initiated the development of several transpressional structural belts in fault bends. In the eastern basin, extensional systems were also superimposed by strike-slip systems. During thermal subsidence, neotectonic movement produced many secondary faults in shallower strata, and the dextral movement of the Tanlu fault zone also altered the eastern basin architecture.